2007
DOI: 10.1631/jzus.2007.b0192
|View full text |Cite
|
Sign up to set email alerts
|

Role of soil rhizobacteria in phytoremediation of heavy metal contaminated soils

Abstract: Heavy metal pollution of soil is a significant environmental problem and has its negative impact on human health and agriculture. Rhizosphere, as an important interface of soil and plant, plays a significant role in phytoremediation of contaminated soil by heavy metals, in which, microbial populations are known to affect heavy metal mobility and availability to the plant through release of chelating agents, acidification, phosphate solubilization and redox changes, and therefore, have potential to enhance phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
159
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(173 citation statements)
references
References 147 publications
(158 reference statements)
1
159
1
3
Order By: Relevance
“…Phytoremediation is a promising technology using plants and microbes to clean up contaminated air, soil and water (Behera 2014). To reduce the level of metal from polluted soil by these techniques are cheaper, efficient and a more environment friendly (Lone et al 2008;Jing et al 2007). Through phytoremediation technique, the metals are extracted or inactivated from the soil (Lombi et al 2001;Bennett et al 2003).…”
Section: Strategies To Reduce Metal Contamination From Aquatic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Phytoremediation is a promising technology using plants and microbes to clean up contaminated air, soil and water (Behera 2014). To reduce the level of metal from polluted soil by these techniques are cheaper, efficient and a more environment friendly (Lone et al 2008;Jing et al 2007). Through phytoremediation technique, the metals are extracted or inactivated from the soil (Lombi et al 2001;Bennett et al 2003).…”
Section: Strategies To Reduce Metal Contamination From Aquatic Systemmentioning
confidence: 99%
“…The physico-chemical properties (microbial biomass, basal respiration and enzymatic activities) of soil increased in the soil, where hyperaccumulator plant is grown (Jiang et al 2010). Jing et al (2007) have shown that from aqueous solution, the metal can be removed by phytofiltration technique. It involves the use of plants to absorb, concentrate or precipitate metals.…”
Section: Strategies To Reduce Metal Contamination From Aquatic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metals cannot be destroyed biologically; they can only be transformed from one oxidation state or organic compound to another. Remediation of soil contaminated with heavy metals is more diffi cult than the remediation of other contaminations (De Jing et al 2007). Plants are the most important link in the food chain resulting from the transfer of metals from soil to animal organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoavailability of metals is strongly influenced by soil characteristics such as pH, cation exchange capacity (CEC), or organic matter content, any of which may limit successful soil remediation (Kayser et al 2000). One promising strategy to improve all these soil characteristics is microorganism-assisted phytoextraction, which rapidly ensures availability of metals by releasing compounds that can desorb metals from the soil matrix to form water-soluble metal complexes into the soil solution for plant uptake (Gadd 1993(Gadd , 2004Guo et al 1996;Jing et al 2007). Although recent studies have revealed that rhizospheric microorganisms are capable of enhancing metal phytoremediation (Carlot et al 2002;Abou-Shanab et al 2003a), as they are able to tolerate, survive and succeed when used in phytoremediation practices (Lucy and Glick 2004), the search for efficient plant-microbe interaction for this purpose is warranted.…”
Section: Introductionmentioning
confidence: 99%